CORRELATION BETWEEN CLASSROOM MANAGEMENT AND MATHEMATICS LEARNING OUTCOMES TO FIFTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN KEBUMEN SUB-DISTRICT IN ACADEMIC YEAR 2019/2020 - Saputra, Aprilia Eka; Joharman, Joharman; Rokhmaniyah, Rokhmaniyah (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
The study aimed to prove the correlation between classroom management and mathematics learning outcomes to fifth grade students of public elementary schools in Kebumen Sub-District and to determine the contribution of classroom management on mathematics learning outcomes to fifth grade students of public elementary schools in Kebumen Sub-District in academic year 2019/2020. The samples were fifth grade students in twelve public elementary schools in Kebumen Sub-District. The study was quantitative correlational method and the instruments were questionnaires about classroom management and mathematics test. The data analysis used simple correlation. The data validity included validity test and reliability test. The results showed that classroom management had positive and significant correlation on mathematics learning outcomes to fifth grade students of public elementary schools in Kebumen Sub-District. The value of Sig. (1-tailed) was 0.002 (<0.005) and considered as moderate correlation (0.472). Adjusted R square of classroom management on mathematics learning outcomes was 22%.